2015
DOI: 10.1039/c4ra12324g
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium nanoparticle-intercalated montmorillonite clay for solvent-free alkene hydrogenation reaction

Abstract: Well characterized ruthenium nanoparticles intercalated montmorillonite clay was used as a catalyst for solvent free alkene hydrogenation reaction and the corresponding products were obtained in good yield. The catalytic activity of ruthenium nanoparticles intercalated montmorillonite clay was successfully tested for 16 different functionalized and non-functionalized alkenes. Apart from alkene reduction, the ruthenium nanoparticles intercalated montmorillonite clay was also applied for Wittig-type reaction for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…truncatifolia (F. F. muscicola) caught our attention. A literature survey revealed that the recent syntheses of the same uses Ru nps relying on hydrogenation reactions under high pressure conditions . The other report by Alonso et al used organic solvents and other pyrophoric reactants .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…truncatifolia (F. F. muscicola) caught our attention. A literature survey revealed that the recent syntheses of the same uses Ru nps relying on hydrogenation reactions under high pressure conditions . The other report by Alonso et al used organic solvents and other pyrophoric reactants .…”
Section: Resultsmentioning
confidence: 99%
“…A literature survey revealed that the recent syntheses of the same uses Ru nps relying on hydrogenation reactions under high pressure conditions. 121 The other report by Alonso et al used organic solvents and other pyrophoric reactants. 83 The recent synthesis of Batatasin III and other analogues also relies on Wittig and olefin reduction in flammable solvents.…”
Section: Acs Sustainable Chemistry and Engineeringmentioning
confidence: 99%
“…Therefore, researchers have been working on solvent-free conditions for both the laboratory synthesis and the industrial manufacturing [1,2]. Some recent works on this direction include the Hantzsch reaction [3], the alkene hydrogenation reaction [4], the alcohol and aldehyde oxidation over Au/MgO [5], and the alkylation of amines with alcohols over organo-iridium catalysts [6].…”
Section: Introductionmentioning
confidence: 99%
“…These catalytic systems include NaBH 4 /NiCl 2 $6H 2 O/moist alumina in hexane, 12 InCl 3 -NaBH 4 reagent system, 13 NaBH 4 /RuCl 3 under aqueous conditions, 14 NaBH 4 /CH 3 COOH in the presence of Pd/C 15 and NaBH 4 -RANEY® nickel system in water. 16 Nevertheless, most of these systems require costly transition metal catalyst, long reaction time and a large excess of NaBH 4 . In addition to this, little has been done to recycle the catalyst for the reduction of alkenes using NaBH 4 .…”
mentioning
confidence: 99%
“…25 The activity of the in situ generated Ni (0) NPs catalyst in EtOH/PEG-400 (3/2 ratio) had also been compared with the commercial RANEY® nickel catalyst. The results revealed that the in situ generated Ni (0) NPs exhibited a higher activity for the reduction of styrene (entries 4,20). Thus, we can conclude that the EtOH/ PEG-400 using NiCl 2 $6H 2 O-NaBH 4 is a very simple and efficient system for the reduction of styrene.…”
mentioning
confidence: 99%